Big data-driven process automation in an API-first fintech company : applied use cases from operations - Sabah, Tanzil Al; Attaphongse Taparugssanagorn; Chaklam Silpasuwanchai; Chantri Polprasert; AIT Scholarship (Pathum Thani, Thailand : Asian Institute of Technology, 2025)
In this report, I present my internship experience at Swan, a leading embedded banking f intech platform, whereIworkedondesigning, developing, anddeployingmultipleoper ational automation workflowsbuiltontopofSwan{u2019}sbigdatamanagementinfrastructure. My work focused on process automation leveraging Swan{u2019}s API-first platform, work f loworchestration tools (NextMatter, Make), partner CRM (Zendesk), and advanced AI integrations (OpenAI API models) for KYC onboarding support. Through several de tailed automation use cases{u2013}includingAI-supportedKYConboarding, adebtcollection workflow, aregulatory fund seizure communication process, real-time operational dash boards, andbulkoperationsviainternal tools{u2013} I demonstrate howcombiningrobustdata modeling with modern automation orchestration platforms can greatly enhance opera tional efficiency, ensure regulatory compliance, and improve customer experience in a highly regulated fintech environment.
An Internship Study submitted in partial fulfillment of the requirements for the degree of Master of Science in Internet of Things (IoT) Systems Engineering
Internship Report (M. Sc.) - Asian Institute of Technology, 2025
Keywords: Financial services industry -- Technological innovations; Big data